The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/catal6120199
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Concentrated Vinyl Acetylene Mixed C4 by Modified Pd Catalysts: Effect of Cu

Abstract: Abstract:The Pd and Pd-Cu on alumina catalysts were tested for hydrogenation of vinyl acetylene in mixed C4 in a circulating tubular reactor. The results showed that adding proper amounts of Cu improved the reaction activity, but inhibited 1,3-butadiene selectivity. Moreover, the presence of Cu retarded the carbon deposition on catalysts during the reaction. Temperature programmed oxidation (TPO), Temperature programmed reduction (TPR), H 2 chemisorption, and X-ray photoelectron spectroscopy (XPS) were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The more reactive ability of PdHx species than bare Pd in the selective hydrogenation of alkynes and olefins has also been reported by Egorov et al 159,160 During the light alkenes selective hydrogenation process, metal catalysts often suffer poor durability due to heavy coke formation. 161,162 To avoid carbon deposition and disrupt chain growth, Lu et al synthesized a microporous alumina layer overcoated Pd/Al 2 O 3 catalyst using atomic layer deposition (ALD) technologies. 163 The porous-layer-coated Pd/Al 2 O 3 catalyst shows remarkably enhanced selectivity to butenes in the selective hydrogenation of 1,3-butadiene, which preserves 100% butenes selectivity at a 1,3-butadiene conversion near 100% even in the presence of excessive propene.…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…The more reactive ability of PdHx species than bare Pd in the selective hydrogenation of alkynes and olefins has also been reported by Egorov et al 159,160 During the light alkenes selective hydrogenation process, metal catalysts often suffer poor durability due to heavy coke formation. 161,162 To avoid carbon deposition and disrupt chain growth, Lu et al synthesized a microporous alumina layer overcoated Pd/Al 2 O 3 catalyst using atomic layer deposition (ALD) technologies. 163 The porous-layer-coated Pd/Al 2 O 3 catalyst shows remarkably enhanced selectivity to butenes in the selective hydrogenation of 1,3-butadiene, which preserves 100% butenes selectivity at a 1,3-butadiene conversion near 100% even in the presence of excessive propene.…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%
“…Zhang et al also reported the porous alumina-supported RuPd catalysts that selectively hydrogenate dimethyl terephthalate (DMT) into dimethyl cyclohexane-1,4-dicarboxylate (DMCD), both the reactant and product are significant for polymer modification. 134,162 The bimetallic PdRu catalysts outperform the monometallic catalysts due to the synergistic effect in RuPd systems, which facilitates strong interactions between Pd and Ru components and between the metals and supports. Furthermore, driven by the increased number of anchoring sites on the porous alumina surface, the supports induced morphological features of active metal, including the smaller nanoparticle size, narrower and more homogenous distribution, and prevented particle aggregation, are present in the porous aluminasupported catalyst.…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%
“…Selective semihydrogenation of concentrated vinyl acetylene in mixed C4, generated from the butadiene extraction process, is carried out due to safety reasons. Insorn and Kitiyanan 143 have compared the selectivity of this reaction using Pd@Al 2 O 3 and different PdCu@Al 2 O 3 catalysts prepared by incipient wetness impregnation. The 1,3-butadiene selectivity was not significantly changed by adding Cu to Pd@Al 2 O 3 .…”
Section: Semihydrogenation Of Alkynesmentioning
confidence: 99%
“…As for the electronic effect, there is electron transfer between the Pd active component and external metals, which changes the valence state of the Pd component as well as the adsorption energy of reaction intermediates on the catalyst surface. Binary alloy catalysts such as PdCu, 31,32 AuCu 33 and PdAg [34][35][36] have also been reported to exhibit high butene selectivity and superior stability in the hydrogenation reaction of 1,3-butadiene due to electronic and geometric effects. Therefore, bimetallic alloying is attractive as a Pd-based catalyst optimization strategy for the hydrogenation reaction of diolens.…”
Section: Introductionmentioning
confidence: 99%